ANALISIS PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI INTERNAL, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN KOPERASI AGROBISNIS TARUTAMA NUSANTARA (KOPA TTN) JEMBER - Sugiarto, Cuk (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: The purpose of this research are to verify the influence of leadership style to effectivity work performance at KOPA TTN Jember, to verify the influence of internal communication to effectivity work performance at KOPA TTN Jember, to verify the influence of organizational culture to effectivity work performance at KOPA TTN Jember, to verify the influence of employes dicipline to effectivity work performance at KOPA TTN Jember, to verify the influence of the most dominant between the fourth variable to effectivity work performance at KOPA TTN Jember. The approach of this research is explanatory researc, the population which consist by Koperasi Agrobisnis Tarutama Nusantara (Kopa TTN) Jember employes as much sixty (60) sampel. F test is used to analyse the influence between the variable simultantly and to verify the causal relations parsially is using t test. Based of analyse result known that the leadership style have an positive effect ad significant to effectivity work, whereas internal communication have an positive effect ad significant to effectivity work, the organization culture have an positive effect ad significant to effectivity work, whereas employes dicipline have an positive effect ad significant to effectivity work, and the most dominant variable have an positive effect ad significant to effectivity work is employes dicipline.Keywords: Leadership Style, Internal Communication, Organizational Culture, Employes Dicipline and Effectivity Work.